GAYA HIDUP DAN SHOPPING ADDICTION - Prasetyo, Yanto (Persona:Jurnal Psikologi Indonesia, 2017)
Abstract                 This study aims to determine the relationship of lifestyle with shopping addiction in students. The hypothesis proposed is that there is a link between lifestyle and student shopping addiction. The subject of this research is high school students 17 August 1945 Surabaya who is currently in class XI. The sample in this study amounted to 55 students taken using random sampling technique. The data were collected using two scales: lifestyle scale to reveal the lifestyle level of a person and the scale of shopping addiction to reveal the level of shopping addiction. Testing of major hypothesis done by using product moment analysis and show a very significant relation between lifestyle with shopping addiction of student with r xy = 0,662; p = 0.000 (p <0.010). When comparing the mean empirical value and the theoretical mean indicating the average lifestyle and shopping addiction of students is high.              Keywords: Lifestyle, Shopping addiction